2021
DOI: 10.1007/s11116-021-10231-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender, mental health and travel

Abstract: It can be accessed at https://rdcu.be/cxunw. This version of the article has been accepted for publication, after peer review, but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For example, it pertains to HEI social psychology themes (Hernandez et al, 2023), addressing anxiety management by leveraging past positive experiences. Additionally, IDC is relevant to digital behaviour fields, such as knowledge management based on blended learning (Tang & Hew, 2022), target skill enhancement in HEI extracurricular activities (Nantha, 2022), and individual self-assistance professional trainingto cope with academic pressure (Mackett, 2022). Through this research, the IDC theory expands our understanding the relationship between universal learning interests and practical learning habits by examining human learning creation patterns (Hashim et al, 2021;Muhria, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…For example, it pertains to HEI social psychology themes (Hernandez et al, 2023), addressing anxiety management by leveraging past positive experiences. Additionally, IDC is relevant to digital behaviour fields, such as knowledge management based on blended learning (Tang & Hew, 2022), target skill enhancement in HEI extracurricular activities (Nantha, 2022), and individual self-assistance professional trainingto cope with academic pressure (Mackett, 2022). Through this research, the IDC theory expands our understanding the relationship between universal learning interests and practical learning habits by examining human learning creation patterns (Hashim et al, 2021;Muhria, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…It was a path understand the human intrinsic desire and relevant conduct, and personal improvement (Diwan & Vartanova, 2020;Setyosari & Cahyono, 2021). IDC has the ability to function in numerous domains, including HEI social psychology theme (Hernandez et al, 2023), digital behavior elds (Tang & Hew, 2022), skill enhancement in education service (Nantha, 2022), and individual self-help professional training (Mackett, 2022). The theory has been developed and broadened over time, but it remains a vital contribution to explaining the universal behavior and thought patterns of humans (Hashim et al, 2021;Muhria, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Otegui-Carles et al (2022) showed that accompanied tourists tend to stay in the destination longer than solo travelers; however, other data point to the fact that solo travelers make longer trips than other tourists. Mackett (2021) showed that more females than males significantly suffered from some anxieties when travelling, such as the need for support, concern about way-finding, interacting with fellow travelers and concerns about the failure of the bus, train or car, and more males than females wanted improvements to the traveling environment, such as less clutter on the street. And some studies showed that freedom and self-development were regarded as important motivations for women to travel alone (Bianchi, 2016;Jordan & Gibson, 2005;Osman et al, 2020).…”
Section: Travel Style and Travel Intentionmentioning
confidence: 99%